The Rhetorical Trend in Studying Political Metaphor - Budaev, Edward V.; Chudinov, Anatoly P. (Respectus Philologicus, 2006)
This article deals with the specificity of the theory and practice of the rhetorical trend in studying political metaphor. Most modern scholars carry out research into political metaphor, citing George Lakoff's seminal works on the conceptual metaphor theory. Although Lakoff's contribution to linguistics is beyond doubt, rhetoric and discourse analysis are also considered sources of the modern theory of political metaphor. The rhetorical trend in studying political metaphor in American scientific discourse anteceded the cognitive approach to the concerned phenomenon. One of the earliest investigators of this area was Michael Osborn, whose works on archetypal metaphors were considered the basis for the rhetorical approach to metaphor in political linguistics. Osborn researched politicians' rhetoric and revealed archetypal metaphors as invariable components transcending culture, time, and geography in political communication. Later, linguists tended to focus on revealing archetypal metaphors in political communication; however, the cultural specificity of political metaphors was also under consideration. Some ideas advanced by researchers within the rhetorical trend anticipated Lakoff and Johnson's theses to a certain extent. It is indicative that similar ideas were suggested in Russian linguistics within the trend of stylistics. The rhetorical approach to political metaphor influenced the theory of conceptual metaphor and was considered to be an alternative to it. Yet it is argued that modern scholars of the rhetorical trend are inclined to adopt the heuristics of the cognitive theory of metaphor. Thus, the concurrent development of the trends is characterised by convergence.
Keywords: political linguistics; rhetoric; political metaphor; political discourse; the cognitive theory of metaphor